Condiciones de competencia en el mercado de gas natural de la República Argentina: 1990-2008 - Petrecolla, Diego (2010)
This paper analyses competition conditions in the natural gas market in Argentina since the early 90 when the sector was privatized. These reforms aimed to improve efficiency. In order to achieve this goal, assets where privatized, the market was deregulated and competition was promoted. This paper analyses the effects of these reforms on competition conditions in the natural gas market. Concentration indexes show a high degree of concentration both at the national level and at the different basins. Also concentration has not decreased since the privatization process was launched. Finally, this market also presents high sunk costs that create barriers to entry for the entrance of new competitors.Competition conditions are more consistent with the performance of an oligopoly market. The Competition Authority and the Sectorial Regulator should monitor this performance since this market is not as competitive as it was thought when the sector was privatized.